The Weanling’s Dilemma. Breastfeeding and Socioeconomic Status in 19th-Century Venice - Derosas, Renzo (Historical Life Course Studies, 2025)
Weaning is one of the most crucial steps in an infant's life. This study investigates how families of different socioeconomic conditions coped with weaning and its consequences for infant mortality, using individual-level longitudinal data drawn from the Venetian population register. As in previous studies, breastfeeding patterns are inferred from infant mortality features. However, the approach adopted differs in part from similar research, combining Cox proportional hazards and Aalen additive regression models. Aalen models allow coefficients to vary over time, showing discontinuities that can be interpreted as signs of the start of weaning. The Venetian case reveals a pronounced social gradient: the poorest mothers breastfed for no more than one month, whereas others continued for 6–8 months or longer. This disparity contributed substantially to socioeconomic inequalities in infant mortality.